(untitled) (Ictus, 2023)
Stroke is the second cause of morbidity and mortality in Chile. Mechanical thrombectomy (MT) is a time-dependent therapy that is effective in reducing the probability of functional dependence in cases with arterial ischemic stroke due to large vessel occlusion and non-extensive infarcted tissue volume. With this approach, treatment can only be indicated for around 9% of total acute ischemic stroke (AIS) cases, so assessing additional situations that were not included in the pivotal trials has been the emphasis of multiple recently published studies. We, therefore conducted a systematic review of the literature published between January 2015 and May 2023, prioritizing clinical trials and meta-analyses of individual patients. Evidence on situations that to this day are controversial, such as intravenous thrombolytic bridging therapy, occlusion of medium caliber vessels, extensive ischemic core, low NIHSS, acute stent placement, and use of antiplatelet agents in the first 24 hours, intra-arterial adjuvant thrombolysis, TM in basilar artery occlusion and the radial approach in complex aortic arches. Expanding the indication for MT under new selection criteria, dispensing the use of advanced neuroimaging, and using adjuvant fibrinolytic or antiaggregant therapies in selected cases, seems to be the path to a paradigm shift that allows expanding the number of patients eligible for reperfusion therapy, without significantly increasing the complications associated with the intervention.